The technology in the english language learning with students of youth 1, 2 and 3, at Fine Tuned English language institute. Academic year 2011-2012 - Pinzón Pardo, Edison Michael (2015)
The present research work entitled “THE TECHNOLOGY IN THE ENGLISH LANGUAGE LEARNING WITH STUDENTS OF YOUTH LEVEL 1, 2 AND 3, AT “FINE TUNE ENGLISH” LANGUAGE INSTITUTE. ACADEMIC YEAR 2011-2012. This theme has been developed with the purpose to contribute to the quality of English language acquisition. The general objective was to find out about the influence of technology on the English language learning with students at Fine Tuned English Language Institute during the academic period 2011-2012. The methods used in this research were: the scientific, descriptive and analytic, synthetic. The surveys were applied to all 5 teachers and all students of youth 1, 2 and 3, at Fined Tuned English Language Institute. Likewise, the results showed that the use of technology in the English language learning can become a good way to teach students to develop higher levels of understanding.